SUPERVISION OF WASTE MANAGEMENT AT SEMARANG CITY - Zirgantara, Ikhsan; Dwimawanti, Ida Hayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
One of the crucial problems in urban areas is the problem of waste. Lots of big cities in Indonesia are overwhelmed with handling waste including the city of Semarang. Along with the increase in population, lifestyles and consumption patterns of community contribute to producing waste in the city of Semarang. The Environmental Services (DLH) is the agency responsible for waste problems that occur in the city of Semarang, in this case carried out by the implementing Technical Service Unit (UPTD) cleanliness of Region I-VIII as implementing operational and technical elements of supporting the Environmental Services in the field.UPTD has the task of carrying out part of the operational technical activities of the Environmental Agency including cleaning services in the area. The purpose of this research was to analyze the supervision carried out by the Environment Services and obstacles faced in monitoring waste management in the city of Semarang. The research method used is descriptive qualitative methods. Data collection techniques are observation, interviews, documentation and data triangulation. The indicator used to assess the activities of supervisory is standard setting, job measurement, comparison, and corrective action. Based on these indicators it can be know what are the obstacles in the process of supervision waste management. The results of the study showed that supervision of the implementation of waste management still has not been optimal because there are still constraints encountered in the supervision process. These constraints are such as the lack of human resources possessed in conducting supervision, lack of facilities and infrastructure, and lack of public awareness in keeping the environment. The advice that researchers gave was to increase the number of human resources in supervision, improve facilities and infrastructure, improve socialization activities to the public on the importance of protecting the environment and and increased synergy with related agency to enforce regulation.